A ready-to-use, versatile, multiplex-able three-dimensional scaffold-based immunoassay chip for high throughput hepatotoxicity evaluation1. Issue 12 (21st June 2015) - Yan, Xiaojun; Wang, Jingyu; Zhu, Lu; Lowrey, Jonathan Joseph; Zhang, Yuanyuan; Hou, Wei; Dong, Jiahong; Du, Yanan
<x xml:space="preserve">Abstract</x> A ready-to-use 3D scaffold-based immunoChip combined with a 3D cell culture chip for high throughput drug hepatotoxicity evaluation.